ENHANCED RECOVERY AFTER SURGERY IN BARIATRIC SURGERY - REVIEW - Karol Bednarz,; Anita Warzocha,; Magdalena Kowalczyk,; Piotr Pitrus,; Anita Krowiak,; Gabriela Majka,; Karolina Krowiak,; Wiktoria Hander,; Aleksandra Karnas,; Maria Jasiewicz, (International Journal of Innovative Technologies in Social Science, 2025)
Enhanced Recovery After Surgery (ERAS) is a multidisciplinary, evidence-based approach designed to optimize perioperative care, improve patient outcomes, and shorten hospital stays. This review examines the application of ERAS protocols in bariatric surgery—a critical intervention for the management of severe obesity and related comorbidities. Key components of ERAS in this context include preadmission counselling, minimized preoperative fasting, goal-directed fluid therapy, opioid-sparing anaesthesia techniques, and structured postoperative nutritional support. Current evidence indicates that adherence to ERAS protocols significantly reduces postoperative complications, accelerates recovery, and shortens the length of hospitalization. Moreover, ERAS has been associated with decreased incidence of postoperative nausea, improved pain control, and reduced reliance on opioids. The role of anaesthesiologists is pivotal in ERAS implementation, and standardized surgical techniques are essential for ensuring patient safety and consistency of care. Overall, this review highlights the growing importance of ERAS in bariatric surgery, emphasizing its effectiveness in enhancing both short- and long-term outcomes.